2020
DOI: 10.1136/medethics-2020-106753
|View full text |Cite
|
Sign up to set email alerts
|

Military metaphors and pandemic propaganda: unmasking the betrayal of ‘Healthcare Heroes’

Abstract: Dr Caitríona L Cox’s recent article expounds the far-reaching implications of the ‘Healthcare Hero’ metaphor. She presents a detailed overview of heroism in the context of clinical care, revealing that healthcare workers, when portrayed as heroes, face challenges in reconciling unreasonable expectations of personal sacrifice without reciprocity or ample structural support from institutions and the general public. We use narrative medicine, a field primarily concerned with honouring the intersubjective narrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 6 publications
0
13
0
3
Order By: Relevance
“…These preliminary findings provide further insight into the scope of MI and MD experienced by HCWs and provide information that will be central to further research surrounding the moral experiences faced by HCWs during COVID-19. The authors of this review hope to enhance recognition of the universal challenges HCWs experienced globally during the pandemic, while strongly recognizing the need to dismantle the ‘hero narrative’ toward HCWs, which may perpetuate an unhealthy perception of invulnerable and self-sacrificing individuals ( 121 ) and ignore their suffering.…”
Section: Discussionmentioning
confidence: 99%
“…These preliminary findings provide further insight into the scope of MI and MD experienced by HCWs and provide information that will be central to further research surrounding the moral experiences faced by HCWs during COVID-19. The authors of this review hope to enhance recognition of the universal challenges HCWs experienced globally during the pandemic, while strongly recognizing the need to dismantle the ‘hero narrative’ toward HCWs, which may perpetuate an unhealthy perception of invulnerable and self-sacrificing individuals ( 121 ) and ignore their suffering.…”
Section: Discussionmentioning
confidence: 99%
“…Junior doctors were frustrated with being labelled ‘heroes’, with literature suggesting that this metaphor results in junior doctors being portrayed as an expendable sacrifice, 39 or diverts attention away from government errors 40 . Few participants discussed utilising formal psychological supports, likely due to barriers including time pressures and difficulty accessing face‐to‐face care 36 .…”
Section: Discussionmentioning
confidence: 99%
“…37 Further, in a survey of non-HCW adults from the United States and Canada, over one-quarter of respondents believed that HCW should have severe restrictions placed on their freedoms, and over one-third respondents avoided HCW for fear of infection. 38 Junior doctors were frustrated with being labelled 'heroes', with literature suggesting that this metaphor results in junior doctors being portrayed as an expendable sacrifice, 39 or diverts attention away from government errors. 40 Few participants discussed utilising formal psychological supports, likely due to barriers including time pressures and difficulty accessing face-to-face care.…”
Section: Discussionmentioning
confidence: 99%
“…The theme raised is dominated by the medical area, such as those related to the pandemic, and Covid 19. One of which is Military Metaphors and Pandemic Propaganda: Unmasking the Betrayal of a Health Care Hero which discusses narrative medicine, related to the inter subjective narrative of patients and service providers as a concept of Heroes in serving Health raises military metaphors, anti-science discourse, and xenophobia in the U.S (Khan, Iwai , and DasGupta, 2021). Based on the results above, it can be identified that the construction of the female hero concept in society in 2020 is dominated by tasks related to the aspects of 'serving', kindness, benefiting others and the community, and being in the domestic space.…”
Section: Discussionmentioning
confidence: 99%